The Risk of Late Treatment and The Reaction of Leprosy with Grade 2 Disability - fariska firdaus (Universitas Airlangga, 2019)
Background: The number of new cases of leprosy in Indonesia is still high with 15,910 new cases found in 2017. East Java is the highest contributor to new leprosy cases with 3,374 incidences in 2017 and the leprosy proportion of the grade 2 disability not reaching the national target is more than 5%. Purpose: This study aimed to analyze the risk of late treatment and the reaction of grade 2 disability of leprosy at Sumberglagah leprosy Hospital, Mojokerto. Methods: This study was the observational type with case-control design. The sample size consists of 35 case samples and 35 control samples. The direct interview and medical records collection were applied in this study. The research was conducted in Sumberglagah Leprosy Hospital from October to November 2018. Several variables were evaluated including the respondent characteristics (gender, age, education level, occupation, and type of leprosy), late treatment, and leprosy reaction. The chi-square test was used in this study. Results: The most Leprosy patients with grade 2 disability were found in the male (31.40%), older citizen (20.00%), people graduated only from elementary school (18.60%), farmers (15.70%), and people experience type-MB leprosy (50.00%). Research conducted at Sumberglagah leprosy Hospital showed the risk of late treatment (p = 0.01) and leprosy reaction (p = 0.01) with grade 2 disability. Conclusion: Late treatment and a history of leprosy reactions cause grade 2 disability in leprosy patients.